EDUKASI PENCEGAHAN PENYAKIT YANG DISEBABKAN BAKTERI YANG TERDAPAT DIDALAM AIR DI WILAYAH KERJA PUSKESMAS PENURUNAN KOTA BENGKULU (STIKes Mitra Keluarga, 2024)
Based on data from the Bengkulu Provincial Health Service in 2023, Diarrhea cases rank 19th out of 56 cases of the most diseases with a total of 2,975 cases in Bengkulu Province. The most common cause of diarrhea cases is the lack of public knowledge about the quality of clean water which is free from microorganisms, especially bacteria. This service aims toprovide education about preventing diseases caused by bacteria found in water in the community in the work area of the Penurunan City Health center, Bengkulu city. The method of this service is health education and discussions which were carried out on April 5 2024 involving 20 people. The implementation of the outreach can be categorized as successful and running smoothly, and the results of the evaluation to the community are that they said that after receiving education/information they knew and understood the quality of water that was suitable for use as drinking water. The conclusion of this service activity is that in general it can increace community knowledge and health education methods are effective in stimulating the community to take action to prevent diseases caused by bacteria found in water, specially Escherichia coli bacteria which can cause diarrhea.